Experimental Study on Using Cement Kiln Dust and Plastic Bottle Waste to Improve the Geotechnical Characteristics of Expansive Soils in Sulaimani City, Northern Iraq (Journal of Engineering, 2022)
In this study, stabilization of expansive soils using waste materials namely; Cement Kiln Dust (CKD), and waste plastic bottles (WPB) was experimentally investigated. Using CKD and WPB are exponentially increasing day by day, due to their capability to solve both environmental and geotechnical problems successfully. Expansive soils were collected from locations with a wide range of plasticity index (PI) (15 - 27) and liquid limit (LL) (35% - 64%). Stabilizer percentages were varied from 0% to 20%, and curing durations for CKD cases were 7 and 28 days. Results showed the best percentages of CKD and WPB are 12% of each one respectively. LL, plastic limit (PL), and swelling percent (SP) loss were observed, which are 46%, 55%, and 96% respectively, and a CBR increase that is 98% with the addition of a mixture of both CKD and WPB was obtained. The best percentage of the utilized stabilization materials are the mixture of 12% CKD and 12% WPB after 28 days curing.